Photodegradation-Adsorption of Organic Dyes Using Immobilized Chitosan Supported Titanium Dioxide Photocatalyst - Lee, Kong Hui (2007)
The combination effect of photodegradation-adsorption using the immobilized TiO2 and chitosan supported on glass (TiO2-Chitosan/Glass) under the illumination of light with suitable energy ( hν > Ebg ) as a new method for the treatment or pre-treatment of dye-containing wastewater has been studied. The prepared photocatalyst was characterized by scanning electron microscopy, X-ray microanalysis, X-ray diffraction analysis, Fourier transform infrared spectroscopy, surface area and porosimetry analysis and thermogravimetric analysis. Methyl orange (an anionic dye of the monoazo series) removal was studied based on the effect of TiO2 : Chitosan ratio, photocatalyst loading, initial concentration, light intensity, different light source, temperature and pH. Comparison was also made to dyes with different characteristics, namely methylene blue (a cationic dye) and mixed dyes (a mixture of methyl orange and methylene blue). Methyl orange removal was optimum when the experiment was run using 5 pieces of 4 dip-coated TiO2-Chitosan/Glass (45 mm X 80 mm X 2 mm) and 500 ml of 20 ppm methyl orange solution at 40 °C under the illumination of a 230 V near UV lamp for 6 hours. About 87.0 % of 20 ppm methyl orange can be removed successfully with approximately 9.2 % removal efficiency attributable to photodegradation process and another 77.8 % attributable to adsorption process. Comparatively, approximately 93.8 % or 18.51 ppm of methylene blue can be removed by applying the same condition with approximately 43.7 % removal efficiency attributable to photodegradation process and another 50.1 % attributable to adsorption process. The solution pH was found to have a significant and yet complex effect. Solutions with pH 4.0 – 6.0 and 10.0 – 12.0 were found to be the optimum range for methyl orange and methylene blue respectively. In view of the electrostatic attraction between the catalyst and substrates, the ionic characteristic of the dyes is suggested to play an important and selective role in both the photodegradation and adsorption processes. The adsorption of model pollutant solutes on the prepared TiO2-Chitosan photocatalyst surface leads to the effective photodegradation process. Removal rate of methyl orange and methylene blue were studied based on the integrated form of Langmuir-Hinshelwood kinetic equations. The photodegradation-adsorption process obeys first order kinetics for the first 60 minutes. After that, it was most likely to be affected by the solution pH and the nature of the photocatalyst. This is obvious based on the effect of pH for MO and MB removal, in which the obtained data cannot fit nicely into the kinetic model or its linearized form. Although Total Organic Carbon (TOC) and Gas Chromatography-Mass Spectrometry (GS/MS) coupled with Direct Insertion-Mass Spectrometry (DI/MS) analyses had confirmed the successful break up of methyl orange and methylene blue ‘parent molecule’, successful destruction of methylene blue aromatic rings is quite difficult to achieve. Nevertheless, the combined photodegradation-adsorption system still appears to be an efficient accelerated removal process of organic pollutants from waste water.